2015
DOI: 10.1007/s11136-015-0923-9
|View full text |Cite
|
Sign up to set email alerts
|

The STOP-BANG questionnaire: reliability and validity of the Persian version in sleep clinic population

Abstract: Persian version of the STOP-BANG performs similar to its original version and is an easy-to-use questionnaire which could be considered as a reliable and valid tool for OSA screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 22 publications
0
45
0
15
Order By: Relevance
“…62 We identified ten studies, involving primarily middle-aged, obese males suspected of OSA that evaluated the performance of STOP-BANG questionnaire against PSG in the identification patients with OSA. 42,[49][50][51][52][63][64][65][66][67] The overall findings reveal that the STOP-BANG questionnaire had high sensitivity, but low specificity for the detection of OSA. These findings became more pronounced when higher levels of OSA category cutoffs were considered.…”
Section: Stop-bang Questionnairementioning
confidence: 99%
“…62 We identified ten studies, involving primarily middle-aged, obese males suspected of OSA that evaluated the performance of STOP-BANG questionnaire against PSG in the identification patients with OSA. 42,[49][50][51][52][63][64][65][66][67] The overall findings reveal that the STOP-BANG questionnaire had high sensitivity, but low specificity for the detection of OSA. These findings became more pronounced when higher levels of OSA category cutoffs were considered.…”
Section: Stop-bang Questionnairementioning
confidence: 99%
“…In previous studies, the agreement of the STOP questionnaire was across a high range of 88-96%. 6,14 In conclusion, we demonstrated that the STOP-Bang or STOP questionnaire represents a useful screening tool for identification of Korean RBD patients at high risk for OSA.…”
Section: Discussionmentioning
confidence: 73%
“…Three or more positive answers from eight items is considered a sign of high risk OSA during sleep (abnormal status). The psychometric properties of the Persian version of STOP-BANG was verified by Sadeghniat, et al 39 Safety Performance Both reactive and proactive measures of safety performance were collected. Occupational incidents were measured by asking participants to report any occupational accidents or near-misses they had experienced in the past month-lagging indicator, and reactive measure of safety performance.…”
Section: Socio-demographic and Work-related Variablesmentioning
confidence: 99%